Analisis Metode Game-Based Learning Dalam Pembelajaran Matematika Kelas Iv Di Sdn Tanjung Jati 2 Bangkalan - Islami, Bastia Fatwa; Mariska, Tria Shinta; Mariska, Faizatul; Istitoah, Istitoah; Kartika, Amanda Yulia; Pratikno, Ahmad Sudi (J-SES : Journal of Science, Education and Studies, 2025)
This study analyzes the application of the game-based learning (GBL) method in mathematics learning in grade IV of Elementary School of Tanjung Jati 2 Bangkalan using a descriptive qualitative approach. The goal is to increase student engagement and understanding. Data were collected through interviews with teachers and direct observation. The results of the study revealed several problems, such as the use of conventional media, limited props, and lack of parental support. Teachers also find it difficult to use IT media, even though students are enthusiastic about digital learning. In addition, students' learning styles are diverse, so a varied approach is needed. Teachers try to overcome this challenge by making learning media simple and communicating with students' parents. They also hope that there will be additional facilities and periodic training. The research findings show that GBL has the potential to improve the quality of mathematics learning, but it needs collaborative support between schools, parents, and related parties to create an optimal learning environment.